Another new, diminutive Rock Gecko (Cnemaspis Strauch) from Peninsular Malaysia and a discussion of resource partitioning in sympatric species pairs - Grismer, L. Lee; Onn, Chan Kin; Quah, Evan; Muin, Mohd Abdul; Savage, Anna E.; Grismer, Jesse L.; Ahmad, Norhayati; Greer Iii, Lee F.; Remegio, Ana-Caroline (Zootaxa, 2010)
A new, diminutive species of Rock Gecko, Cnemaspis shahruli sp. nov. from Penang Island, Penang; Pulau Jerejak, Penang; Pulau Pangkor, Perak; and the adjacent mainland at Sungai Sedim, Kedah was previously confused with juveniles of the sympatric, endemic species C. affinis (Stoliczka) on Penang Island. Cnemaspis shahruli sp. nov. is diagnosed from all other Southeast Asian Cnemaspis on the basis of several unique aspects of squamation, coloration, and body size. It is proposed that this new species has a more extensive mainland distribution than is presented here based on its southernmost record on Pulau Pangkor, Perak. A pattern of resource partitioning on the basis of body size, habitat, and activity period among sympatric species pairs of Cnemaspis is discussed.